Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Gap Between Inner Casing and Stator Blade on Axial Compressor Performance

Abstract: The small gap at stator hub section of 10-stage axial compressor of small power class industrial gas turbine engine was studied to confirm its effect on compressor analysis result. This gap is allowed for manufactural tolerance and thermal expansion during engine operation. For the convenient purpose of CFD geometric modeling, such gap was simplified and the 3D Navier-Stokes code was used to predict the compressor performance then compared the results with the case without a gap. In the case of calculation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Currently, research on flow separation with regard to axial-flow compressors is more extensive than that for axial-flow pumps, providing valuable insights for this study. Based on existing research, it is known that flow separation is primarily influenced by structural differences, such as hub gaps, blade thickness, and area ratio [10][11][12]. For instance, Lee et al [10] found that in multi-stage axial-flow compressors, the presence of stator hub gaps reduces the pressure ratio of the compressor, eliminating flow separation in the hub corner and improving compressor performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, research on flow separation with regard to axial-flow compressors is more extensive than that for axial-flow pumps, providing valuable insights for this study. Based on existing research, it is known that flow separation is primarily influenced by structural differences, such as hub gaps, blade thickness, and area ratio [10][11][12]. For instance, Lee et al [10] found that in multi-stage axial-flow compressors, the presence of stator hub gaps reduces the pressure ratio of the compressor, eliminating flow separation in the hub corner and improving compressor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Goel et al [11] discovered that when the thickness of guide vane blades decreases, the pressure changes on the suction side of the blades become smoother, reducing flow separation and enhancing the hydraulic performance of the pump. Liu et al [12] found that increasing the area ratio of the guide vane causes severe separation of the fluid from the surface of the blade, resulting in complex flow phenomena such as backflow, secondary flow, and vortices. This weakens the constraint ability of the guide vane on the fluid motion, increases hydraulic losses, and subsequently affects the pump's optimal efficiency and high-efficiency region.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted about the detailed flow mechanism of the interplay between these two secondary flows. Many studies have suggested that the corner separation is weakened by the leakage flow, which suppresses the migration of the low energy flow [1,3,[5][6][7], while Dong et al [8] thought that the leakage flow has an energizing effect on the low energy flow in the corner, which is the primary reason for the suppression of corner separation, and Gbadebo et al [9] noted that the elimination of the corner separation is caused by the suppression of the horseshoe vortex in the leading edge. In total, there is still no uniform conclusion on this question.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the flow mechanism of the interaction between the leakage flow and the corner separation. For example, Dean [15], Lakshminarayana and Horlock [18], Singh and Ginder [19], Lee, et al [20], and George, et al [21] thought it is the suppression of the migration of the low energy flow by the leakage flow that weakens the corner separation, while Gbadebo, et al [22] pointed out that it is the suppression of the horseshoe vortex in the leading edge that causes the removal of the corner separation, and Dong, et al [23] considered that the suppression of corner separation is mainly caused by the mixing of the high energy leakage flow with the low energy flow in the corner. The second one is the effect of the clearance size on the compressor or the cascade performance.…”
Section: Introductionmentioning
confidence: 99%